Methods for estimating beneficiary populations targeted by health and nutrition interventions for women, pregnant women, infants, and young children - Gune, Soyra; Nguyen, Phuong Hong; Chakrabarti, Suman (Oxford University Press, 2025)
Utilization of maternal and child interventions is typically tracked in low- and middle-income countries (LMICs) using coverage estimates from population representative surveys. These estimates cannot be directly applied to assess resource gaps in intervention delivery for which data on the population eligible is required. Moreover, coverage improvements may not necessarily reflect an expansion in utilization because of a decline in the population eligible. We develop a method to estimate the populations eligible for interventions across the continuum of care. The method uses data from the World Population Prospects and the Demographic Health Survey, data sources which are available for most LMICs. Additionally, we develop a method to estimate the eligible population covered by each intervention. Using the illustration of India, we estimate populations eligible for, and covered by interventions during preconception, pregnancy, delivery, lactation, and childhood. We find that between 2015 and 2020, the eligible population declined for all beneficiary groups. Additionally, coverage expansion was not entirely driven by an increase in the population accessing an intervention, but rather also by a decline in the eligible population. Our illustration highlights the importance of including population estimates alongside coverage for interventions, particularly in LMIC contexts due to changing fertility dynamics.